Methodology for developing a web configurator for technology cabinets - Shafik Shaehovich Khuzyatov; Lenar Ajratovich Galiullin (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Current trends in the development of Internet technologies are very promising, their role in the functioning of enterprises is increasing significantly. Internet technologies are tools that allow you to interact with potential customers and consumers, receive feedback from them. At the same time, factors of physical remoteness are practically nullified. The situation with the rapid development of the Internet market means that in the process of forming the necessary configurations of technological cabinets for industrial facilities management systems, the use of manual labor should be minimized. The standard approach uses paper media, which leads to a large investment of time in the formation of the necessary configurations and the calculation of their cost. In this regard, increases the complexity of the work performed and the likelihood of errors in the calculations. Thus, the following problems can be formed: the lack of sufficient mechanisms for operational interaction with potential customers; time consuming paper handling; the complexity of the operations; high probability of errors in the calculations; lack of operational access to the necessary information.